In silico epitope identification of unique multidrug resistance proteins from Salmonella Typhi for vaccine development. (February 2019) - Jebastin, Thomas; Narayanan, Sundarabaalaji
Graphical abstract: Highlights: We identified B and T-cell epitopes from MDR proteins from Salmonella Typhi. Nine promiscuous T-cell epitopes were identified from S. Typhi MDR proteins. These 9 epitopes are capable of generating humoral and adaptive immune responses. Abstract: Typhoid fever is a multisystemic illness caused by Salmonella enterica serovars Typhi and is resistant to most antibiotics and drugs. The resistance is conferred through multidrug resistance (MDR) proteins, which efflux most antibiotics and other drugs. We predicted potential candidate B-cell and T-cell epitopes using bio- and immune-informatics tools in the 11 MDR proteins - EmrA, EmrB, EmrD, MdtA, MdtB, MdtC, MdtG, MdtH, MdtK, MdtL and TolC. The antigenic potential of the MDR proteins was calculated using VaxiJen server. The B-cell and T-cell epitopes of the MDR proteins were predicted using BCPred and ProPredI and ProPred respectively. The binding affinities of the predicted T-cell epitopes were estimated using T-epitope designer and MHCPred tools. 10, 7, 5, 12, 14, 21, 26, 3, 3 and 3 B-cell epitopes were identified in EmrA, EmrB, EmrD, TolC, MdtA, MdtB, MdtC, MdtG, MdtH and MdtL respectively. We predicted 9 T-cell epitopes - YVSRRAVQP (EmrA), FGVANAISI (EmrB), MVNSQVKQA and YQGGMVNSQ (TolC), WDRTNSHKL (MdtA), FLRNIPTAI (MdtB), YVEQLGVTG (MdtG), VKWMYAIEA (MdtH) and LAHTNTVTL (MdtL) capable of eliciting both humoral and adaptive immune responses. These T-cell epitopes specifically bind to HLA alleles - DRB1*0101 and DRB1*0401. This is the first report of epitope prediction in the MDR proteins of S. Typhi. Taken together, these results indicate the MDR proteins – EmrA, MdtA and TolC are the most suitable vaccine candidates for S. Typhi. The findings of our study on the MDR proteins prove to be useful in the development of peptide-based vaccine for the prevention and/or treatment of typhoid fever.